Design of cities - Bacon, Edmund N. (New York : Penguin Books, 1976)
The purpose of this revised edition is to transmit, not the forms of my work which will be deemed obsolete, but rather the forces behind them, the thought models and the muscular and sensory images on which they were based, and the forces which propelled them into action.
Acknowldegments -- Foreword-revised edition -- Foreword -- The city as act of will -- Awareness of space as experience -- the nature of design -- Ways of perceiving one's self -- The growth of greek cities -- Design order of ancient Rome -- Medieval design -- Upsurge of the renaissance -- Design structure of baroque Rome -- Dutch interlude -- 18th and 19th century European design -- Development of Paris -- Evolution of Saint Petersburg -- John Nash and London -- Vitrivius comes to the new world -- Le Corbusier and the new vision -- The great effort - Brasilia -- Peking -- Simultaneous movement systems -- Decision making -- Putting the ideas to work - Philadelphia -- City for humanity - Stockholm -- Looking into the future -- Appendix -- Notes on illustrations -- Bibliography -- Index.
Includes bibliographical references and index.
Keywords: CITY PLANNING